Effect of vitamin D monotherapy on indices of sarcopenia in community‐dwelling older adults: a systematic review and meta‐analysis. Issue 3 (8th March 2022) - Prokopidis, Konstantinos; Giannos, Panagiotis; Katsikas Triantafyllidis, Konstantinos; Kechagias, Konstantinos S.; Mesinovic, Jakub; Witard, Oliver C.; Scott, David
Abstract: Background: Vitamin D supplementation is proposed as a potentially effective nutritional intervention to mitigate the risk of sarcopenia. The aim of this systematic review and meta‐analysis was to investigate the impact of vitamin D supplementation monotherapy on indices of sarcopenia in community‐dwelling older adults. Methods: A comprehensive search of the literature was conducted in PubMed, Web of Science, Scopus, and Cochrane Library. Eligible randomized controlled trials (RCTs) compared the effect of vitamin D supplementation (as monotherapy) with placebo on indices of sarcopenia in older (>50 years) adults. Using the random effects inverse‐variance model, we calculated the mean difference (MD) in handgrip strength (HGS), short physical performance battery (SPPB), timed up and go (TUG), and appendicular lean mass (ALM) between groups. We also calculated the standardized mean difference (SMD) in general muscle strength and general physical performance (composite plot of all muscle strength and physical performance outcomes, respectively) between groups. Results: Ten RCTs were included in the meta‐analysis. A significant decrease in SPPB scores was observed with vitamin D supplementation compared with placebo (MD: −0.23; 95% CI −0.40 to −0.06; I 2  = 0%; P  = 0.007). Vitamin D supplementation conferred no effect on HGS (MD: −0.07 kg; 95% CI −0.70 to 0.55; I 2  = 51%, P  = 0.82), TUG (MD: 0.07 s; 95% CI −0.08 to 0.22; I 2  = 0%, P  = 0.35), ALM (MD: 0.06 kg/m 2 ; 95% CI: −0.32 to 0.44; I 2  = 73%, P  = 0.77), general muscle strength (SMD: −0.01; 95% CI −0.17 to 0.15; I 2  = 42%, P  = 0.90), or general physical performance (SMD: −0.02; 95% CI −0.23 to 0.18; I 2  = 71%, P  = 0.83). Conclusions: Vitamin D supplementation did not improve any sarcopenia indices in community‐dwelling older adults and may compromise some aspects of physical performance. Future studies are warranted to investigate the impact of vitamin D supplementation on individual indices of SPPB, including mobility and balance, in older adults.